"It's Your Finsta at the End of the Day . . . Kind of": Understanding Emerging Adults' Self-Presentational Changes on Secondary Accounts. (February 2023) - Tao, Michelle; Ellison, Nicole B.
This study explores emerging adults' reflections about how their secondary Instagram account ("Finsta" or Fake Instagram) self-presentation evolved over time, from account creation to their present use. Drawing on interview data collected from female emerging adults ( N = 17) who had at least one Finsta and one Rinsta (i.e., Real Instagram), we use Emerging Adulthood as a frame for understanding how their content-sharing practices changed, reflecting their own development from adolescence to adulthood. Our participants described how their Instagram content-sharing behaviors evolved, reflecting their desire to be seen as more mature, especially in regard to managing negative self-presentational content. Furthermore, some participants described the difficulties introduced by context collapse associated with presenting to two distinct networks, both high school and college followers. Finally, and reflecting contemporary developments, we document how the "Making Rinsta Casual Again" trend and the COVID-19 pandemic influence users' self-presentational behaviors on image-based social media platforms like Instagram.